Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1007/s10741-020-10057-7
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafiltration is better than diuretic therapy for volume-overloaded acute heart failure patients: a meta-analysis

Abstract: Studies on the effectiveness of ultrafiltration (UF) in patients hospitalized with acute decompensated heart failure (ADHF) have led to heterogeneous study outcomes. This meta-analysis aimed to assess the impact of UF therapy in ADHF patients. We searched the medical literature to identify well-designed studies comparing UF with the usual diuretic therapy in this setting. Systematic evaluation of 8 randomized controlled trials enrolling 801 participants showed greater fluid removal (difference in means 1372.5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 28 publications
2
13
0
Order By: Relevance
“…Our results were partly consistent with Wobbe meta-analysis. [ 20 ] Moreover, we updated the review by adding 4 more studies, and heterogeneity was lower in our analysis. Heterogeneity still existed in weight loss regardless of sensitivity analysis, but not in fluid loss.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results were partly consistent with Wobbe meta-analysis. [ 20 ] Moreover, we updated the review by adding 4 more studies, and heterogeneity was lower in our analysis. Heterogeneity still existed in weight loss regardless of sensitivity analysis, but not in fluid loss.…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis of Wobbe et al [ 20 ] suggested that UF is a safe and effective treatment without a difference in renal impairment, and lower incidences of worsening heart failure. Shi et al [ 21 ] concluded that UF did not have a difference in worsening heart failure, cardiovascular outcome, hemorrhage, the change of serum creatinine and infection, but not in hypotension.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed greater fluid removal and weight loss, and lower incidence of worsening HF and rehospitalizations for HF, without effects on renal function and all-cause mortality. 40 Regrettably, neither of these studies evaluated the incidence of adverse effects, such as catheter related infections, filter clotting, etc.…”
Section: Clinical Trials Comparing Uf and Diuretic Treatmentmentioning
confidence: 99%
“…64 UF is better than diuretics regarding fluid removal rate and weight loss and reduces rehospitalization rate. 65 So, UF improves quality of life decrease morbidity but have no impact upon mortality. 65 Nevertheless, several studies are not benefiting from UF.…”
Section: Introduction: Pathophysiology and Rationale Of Ultrafiltrationmentioning
confidence: 99%
“…65 So, UF improves quality of life decrease morbidity but have no impact upon mortality. 65 Nevertheless, several studies are not benefiting from UF. For instance, background UF is not commonly used because of higher incidence of worsening renal function without improved decongestion.…”
Section: Introduction: Pathophysiology and Rationale Of Ultrafiltrationmentioning
confidence: 99%